Integrated Marketing Communication Munching Queen dalam Meningkatkan Penjualan Produk Kids Friendly Snack - Khilmi, Rifqi Muslim (Jurnal Nomosleca, 2024)
In this era of competition, the variety of snack products for children has increased and the variety requires a good and well-targeted marketing strategy. Marketing is not just about personally selling or buying products, but communicating with customers both directly and indirectly must be one of the keys to the success of a marketing strategy. The Munching Queen is one of the UMKM which is said to be successful in selling its products. This success certainly cannot be separated from marketing strategies in various forms, one of which is Integrated Marketing Communication (IMC). The results show that it has succeeded, starting from direct marketing elements to the use of social media to increase product sales. In the advertising element, it carries out advertising through social media, in sales promotions The Munching regularly holds promotions and discounts on purchases every month. Then in direct marketing by participating in school events and selling directly to consumers, apart from that, The Munching Queen's online marketing activities utilize e-commerce Shopee and Tokopedia and collaborate with playgrounds as well as schools and communities to increase awareness and sales.